Postresuscitative Recovery of Circulation: Pathogenetic Aspects - A. Ya. Yevtushenko; A. S. Razumov; A. V. Budayev; P. S. Razumov (Общая реаниматология)
The paper describes the results of long-term experimental studies of systemic and regional hemodynamics in different animals (dogs, cats, rats), by using various models of dying. Recovery of circulation in the animals that had experienced 5-minute clinical death has been ascertained to be phasic with primary short-term hyperperfusion changing into hypoperfusion, followed by a gradual blood flow normalization. In early perfusion, the flows of blood are shown to be redistributed, causing circulation to be centralized. Excess cerebral hyperperfusion is accompanied by a drastic activation of free radical processes, deteriorated neurological recovery, and decreased survival. Restriction of excess cerebral hyperperfusion via temporary exclusion of a portion of the circulating blood volume, as well as correction of reper-fusion activation of lipid peroxidation with drugs (fridox, emoxipin) substantially improve the processes of neurological recovery and lowers postresuscitative mortality.